The diverging trends of male and female bottom incomes in Germany - Eliana Coschignano; Robin Jessen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Men at the bottom quintile of the German male earnings distribution had lower average earnings in 2019 than in 2001. In contrast, female earnings have increased throughout the distribution. What explains these diverging trends and how did they translate into changes in net income? Data from the Socio-Economic Panel (SOEP) reveal that the drop in bottom male earnings is mostly due to a decrease in work hours, while hours worked of females with low earnings have increased. Changes in socio-demographic characteristics explain little of the evolution of income inequality. Households and the welfare state have cushioned much of low-earning men's income drop, while disposable incomes of women have increased by less than their earnings. Finally, earnings poverty is persistent: About half of individuals in the bottom quintile are still in the bottom quintile after five years. – – Männer im unteren Quintil der deutschen männlichen Einkommensverteilung hatten 2019 niedrigere durchschnittliche Einkünfte als noch 2001. Im Gegensatz dazu sind die Einkünfte von Frauen über die gesamte Verteilung hinweg gestiegen. Was erklärt diese divergierenden Trends und wie haben sie sich auf die Veränderungen im Nettoeinkommen ausgewirkt? Daten aus dem Sozio-oekonomischen Panel (SOEP) zeigen, dass der Rückgang der Einkommen niedriger verdienender Männer hauptsächlich auf einen Rückgang der Arbeitsstunden zurückzuführen ist, während die Arbeitsstunden von Frauen mit niedrigem Einkommen gestiegen sind. Veränderungen in sozio-demografischen Merkmalen erklären wenig der Entwicklung der Einkommensungleichheit. Haushalte und der Wohlfahrtsstaat haben einen großen Teil des Einkommensrückgangs bei Männern im unteren Einkommensbereich abgefedert, während das verfügbare Einkommen der Frauen weniger stark gestiegen ist als deren Einkünfte. Schließlich ist Einkommensarmut beständig: Etwa die Hälfte der Personen im unteren Quintil verbleiben auch nach fünf Jahren noch im unteren Quintil.
Keywords: D31; I38; J3; 330; Income inequality; earnings inequality; working hours; decomposition